IMPLEMENTASI DIMENSI PROFIL PELAJAR PANCASILA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SD NEGERI 2 SUSUT BANGLI - Ni Luh Ekayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Modernization and technological developments not only have positive impacts on students but also have negative impacts. This is a major challenge in the world of education. Therefore, school programs are needed that can be the basic foundation in forming student character. This study aims to determine: (1) the implementation of the Pancasila student profile dimensions in forming the religious character of students at SD Negeri 2 Susut, (2) obstacles in implementing the Pancasila student profile dimensions, (3) implications of its implementation. The method used in this study is a qualitative method and the theory used is the behaviorist theory proposed by Skinner and the social learning theory proposed by Albert Bandura. The results of the study indicate that (1) Religious character is implemented through school programs, namely: intracurricular, co-curricular, extracurricular, dharma wacana, mebanten and puja tri sandya, sacita manuk lensi, jus senang, 5S, suka duka, Sabtu bersih, eco enzyme, flag ceremony, and singing the national anthem. (2) obstacles in the formation of students' religious character, namely: differences in students' cognitive development, lack of student motivation, tight teacher schedules, facilities and infrastructure, and lack of parental supervision. (3) Implications in the application of the dimensions of the Pancasila student profile in forming students' religious character are increased student devotion, the formation of self-discipline, the establishment of good social relations, the formation of harmonious relations with nature or the surrounding environment, and the growth of a sense of love for the homeland.